Terephthalic acid‐directed supramolecular Cu(II)‐metallogel for photosensitive semiconducting Schottky diode with promising electronic charge transportation. (4th November 2020) - Dhibar, Subhendu; Dey, Arka; Majumdar, Santanu; Ray, Partha Pratim; Dey, Biswajit
Summary: Terephthalic acid‐based supramolecular metallogel of Cu(II) (ie, Cu‐TA) is developed by sonicating the mixture of copper(II) acetate monohydrate and terephthalic acid in N, N ‐dimethyl formamide solvent. The rheological study is performed to expose the mechanical property of metallogel. The flake‐like morphological patterns are found through FESEM microstructural investigations. The formation strategy, crystalline nature, and thermal behavior of the Cu‐TA metallogel are also studied. The optical and electrical properties of Cu‐TA metallogel are exhaustively scrutinized, and the measured data show that Cu‐TA metallogel is semiconducting in nature. The electrical analysis indicates that the conductivity of Cu‐TA metallogel increased up to four times under illumination (7.49 × 10 −5 S m −1 ) rather than the nonirradiation condition (1.83 × 10 −5 S m −1 ). The measured I ‐ V characteristics of Cu‐TA metallogel‐based thin‐film metal‐semiconductor (MS) junction devices under irradiation and nonirradiation conditions show a nonlinear rectifying behavior, typical of a Schottky diode (SD). Abstract : Terephthalic acid‐mediated supramolecular Cu(II)‐metallogel is executed to fabricate a photosensitive semiconducting Schottky diode device. The optical and electrical properties of the synthesized metallogel express the semiconducting feature of the Cu(II)‐metallogel. The electrical studies explore that the conductivity of Cu(II)‐metallogel increased to four times under illumination with respect to nonirradiation conditions. I‐V characteristics of Cu(II)‐metallogel‐based thin‐film metal‐semiconductor (MS) junction devices under irradiation and nonirradiation conditions show a nonlinear rectifying behavior, characteristic of a Schottky diode.